Intravascular papillary endothelial hyperplasia: a case report - Nayl, Catherine; Fenelon, Mathilde; Catros, Sylvain; Fricain, Jean-Christophe (Journal of oral medicine and oral surgery, 2019)
Case report: A 71-year-old patient, with no notable medical-surgical history, was referred for a specialized consultation with Oral Mucosal Pathology for tumefaction on the dorsal side of the tongue. It was a nodular lesion measuring one centimeter long, purplish, and painless. There was nothing found through palpation. Surgical excision with a laser diode was performed under local anesthesia. The postoperative follow-up was simple. The patient was seen 3 months later without any sign of recurrence. Histopathological analysis revealed a vegetative intravascular hemangioendothelioma. Comments: This case is rare because of the location of the tumor, and moreover because the subject is male. A laser diode was chosen to resect the lesion because of the purple color which could have resulted in a possible vascular lesion. Indeed, the limits of excision were coagulated, which facilitated the surgery time and any limited postoperative hemorrhagic complications that could have occurred.